2012
DOI: 10.1507/endocrj.ej12-0069
|View full text |Cite
|
Sign up to set email alerts
|

ZnT8 and type 1 diabetes [Review]

Abstract: Abstract. Zinc is essential for the proper storage, secretion, and the action of insulin and is transported from cytoplasm to insulin secretory granules in the pancreatic β-cells by SLC30A zinc transporters (ZnT). ZnT8 is specifically expressed in the pancreatic β-cells and has been identified as a novel target autoantigen in patients with type 1 diabetes. Autoantibodies to ZnT8 (ZnT8A) are detected in 50-60% of Japanese patients with acute-onset and 20% with slow-onset type 1 diabetes. Furthermore, humoral au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Zinc transporters control its homoeostasis. ZnT8 is localised on insulin-containing secretory granule membranes (30). We still do not know whether the same process could be responsible for the development of thyroiditis and share polymorphisms in the SLC30A8 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc transporters control its homoeostasis. ZnT8 is localised on insulin-containing secretory granule membranes (30). We still do not know whether the same process could be responsible for the development of thyroiditis and share polymorphisms in the SLC30A8 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is necessary for structural stability of stored insulin in the β-cells. In pancreatic β-cells, the transport of zinc into the cytoplasm and insulin secretory granules is accomplished by ZnT8 [56] and ZnT8 Ab is one of the major markers for T1DM [57]. A possible association between ZnT8 expression in different tissues and metabolic control in experimental animals has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Wenzlau et al followed the individuals from birth to T1D onset and they found that ZnT8 antibodies (ZnT8A) appeared as early as 2 years of age and showed increasing levels and prevalence persisting to disease onset (Wenzlau et al, 2009;Wenzlau et al, 2007). Some suggested a strong inverse relationship between the age of T1D onset and the prevalence of ZnT8A (Kawasaki, 2012). Our study demonstrated that ZnT8 as a novel autoantigen containing many immunodominant epitopes, which were recognized in type 1 diabetes patients (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 50%
“…As described in some articles, ZnT8 antigen, encoded by the gene SLC30A8, is a major autoantigen in T1D (Kawasaki, 2012). SLC30A8 gene is located on chromosome 8 at the position q24.11 in human.…”
Section: Discussionmentioning
confidence: 99%